The contribution of The Mindfulness and its relationship to risk-taking behavior in predicting sports injury among junior footballers in the Kingdom of Saudi Arabia - Al-Ghamdi, Turki; Haggag, Mohammed (Journal of Physical Education, 2024)
The study aimed to identify the level of mental alertness and risk-taking behavior among soccer players, and to identify the relationship between mental alertness and risk-taking behavior, and to identify the differences in mental alertness and risk-taking behavior in the light of the following demographic variables (training age, degree of injury severity, number of injury times, centers  playing), and knowing the extent of the contribution of mental alertness and its relationship to risky behavior to predict sports injury in football youths, and the study used the descriptive approach, and the study population consisted of junior high-class clubs, and the sample included (300) youths, who were chosen in a simple random way, and the study was used in  The tools are a measure of mental alertness (Johnson, et al, 2016), a measure of risk-taking behavior (Abdel-Fattah, Mahmoud, 2019), and a form for the player's primary data.  There is an inverse (negative) statistically significant correlation between the total degree of mental alertness and risk-taking behavior and its dimensions.  Mental alertness and risk-taking behavior according to the following variables (training age - playing position), and there are statistically significant differences in mental alertness according to the number of sports injuries in the past and current season and the severity of the injury in favor of the players whose number of injuries is from (1-3), and whose severity  Their injury is light, and there are statistically significant differences in the risk-taking behavior according to the number of injury times for the two seasons and the severity of the injury in favor of the players whose number of times of injury is from (1-3) times and whose severity of injury is light, and since the higher the degrees of mental alertness among soccer players, this leads to  The decrease in risk-taking behavior among young people, which is reflected in the reduction of sports injuries, so mental alertness predicted the risk-taking behavior, which was reflected in the decrease in the rate of sports injuries.